Critical Spatial Practices: A Trans-scalar Study of Chinese Hutongs and American Alleyways - Marinic, Gregory; Radtke, Rebekah; Luhan, Gregory (UI Scholars Hub, 2021)
Across time and cultures, the built environment has been fundamentally shaped by forces of occupancy, obsolescence, and change. In an era of increasing political uncertainty and ecological decline, contemporary design practices must respond with critical actions that envision more collaborative and sustainable futures. The concept of critical spatial practice, introduced by architectural historian Jane Rendell, builds on Walter Benjamin and the late 20th century theories of Henri Lefebvre and Michel de Certeau to propose multi-disciplinary design practices that more effectively address contemporary spatial complexities. These theoretical frameworks operate through trans-scalar means to resituate the built environment as a nexus of flows, atmospheres, and narratives (Rendell, 2010). Assuming an analogous relationship to the contemporary city, critical spatial practices traverse space and time to engage issues of migration, informality, globalisation, heterotopia, and ecology. This essay documents an interdisciplinary academic design studio that employed critical spatial practices to study correspondences between Chinese and American cities. Here, the notions of urban and interior are relational. Urbanism and interior spaces are viewed as intertwined aspects in the historical development of Beijing hutongs and Cincinnati alleyways. These hybrid exterior-interior civic spaces create sheltered public worlds and socio-spatial conditions that nurture people and culture.